(3cJGH aj GdUjO hGdbfUs - (3WjHhZG GdCTQaj , WjHhZG GdGTQaj GdHWdeTj GdjhfGfj, YdGA GdOjf,J (B770 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eMce eG GHJYO heJbf eG CNJQY s
(3BNQgG (B:s
(3Ke EPG hdOJ hdOfG cKjQkG Je GdcJGH HMeO Gddg s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B46s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B34 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI HGdEScfOQjI (B(1201(3H(B) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs